Penerapan Buku Digital Kapita Selekta Matematika II Untuk Meningkatkan Hasil Belajar Di Perguruan Tinggi - Muhammad Fathurrahman; Rahmatullah Bin Arsyad; Muhammad Syahrul Kahar (Qalam : Jurnal Ilmu Kependidikan, 2024)
An important aspect in advancing a nation is to enhance the quality of its education, a crucial part of which is the preparation of high-quality teaching materials that are in line with contemporary developments. This research was conducted with the goal of improving student learning outcomes by using a digital book on selected topics in Mathematics II. The study employed the 4D research development method to develop the textbook on selected topics in Mathematics II, which was then applied to third semester mathematics education students. The teaching media was validated by experts competent in language, media, and material aspects. The validation results for the language aspect were 98%, media 95%, and material 99%, indicating that the teaching media is valid. The study found that the average pre-test score was 38.27, while the post-test score was 74.23. Based on the pre-test and post-test results, the n-Gain value of the learning outcomes improvement was 0.6 in the medium category, and the average test score was 79.42 with a classical completeness of 85%. These results demonstrate that the application of the digital book on selected topics in Mathematics II is effective in improving student learning outcomes.